Given matrix M = ((1, 1, 2), (3, 1, 1), (2, 3, 1)) with characteristic equation x^3-3x^2+ax+b = 0, what are the values of a and b ?

2 Answers
Mar 19, 2017

(a, b) = (-7, -11)

Explanation:

Given:

M = ((1, 1, 2), (3, 1, 1), (2, 3, 1))

We find:

M^2 = ((1, 1, 2), (3, 1, 1), (2, 3, 1))((1, 1, 2), (3, 1, 1), (2, 3, 1)) = ((8, 8, 5), (8, 7, 8), (13, 8, 8))

M^3 = ((1, 1, 2), (3, 1, 1), (2, 3, 1))((8, 8, 5), (8, 7, 8), (13, 8, 8)) = ((42, 31, 29), (45, 39, 31), (53, 45, 42))

Then:

M^3-3M^2 = ((42, 31, 29), (45, 39, 31), (53, 45, 42))-((24, 24, 15), (24, 21, 24), (39, 24, 24)) = ((18, 7, 14), (21, 18, 7), (14, 21, 18))

Looking at the off diagonal elements, it is clear that we want to set a=-7 to find:

M^3-3M^2-7M = ((18, 7, 14), (21, 18, 7), (14, 21, 18))-((7, 7, 14), (21, 7, 7), (14, 21, 7)) = ((11, 0, 0), (0, 11, 0), (0, 0, 11))

So put b=-11 to find that the characteristic equation is:

x^3-3x^2-7x-11 = 0

Mar 19, 2017

See below

Explanation:

A beginner's approach.

We get the characteristic equation from the basic idea that for matrix A there exist eigenvalues (lambda's) and eigenvectors (mathbf e's) such that:

A mathbf e = lambda mathbf e implies (A - lambda I) mathbf e = mathbf 0

And to avoid the null solution, ie mathbf e = mathbf 0, we force (A - lambda I) to be singular, ergo its determinant is zero.

So:

det ((1 - lambda, 1, 2), (3, 1 - lambda, 1), (2, 3, 1 - lambda) ) = 0

implies (1-lambda) * det ((1-lambda, 1),(3, 1 - lambda)) - 1 * det ((3,1),(2, 1 - lambda)) + 2 * det ((3, 1 - lambda),(2,3)) = 0

implies (1-lambda) * ((1-lambda)^2 - 3) - 1 * (3(1 - lambda) - 2) + 2 * (9 - 2(1-lambda)) = 0

Which eventually simplifies to:

lambda^3 - 3 lambda^2 - 7 lambda - 11 = 0

Clearly this approach does use the fact you already have the cubic and quadratic terms in the bag, and involves a load of algebra that I declined to typeset, and so is weaker on those grounds alone.